Evaluation of Usability, User Experience, and Accessibility in Health Applications: a Literature Review - Bejarano Salazar, Ana Gabriela (2024)
The following literature review aims to identify platforms related to usability evaluation, user experience, and accessibility in health studies, to outline essential elements for consideration in developing, implementing and assessing of eHealth applications. After retrieving studies, 38 studies related to health and mobile Health (mHealth) were found, involving 1611 users in evaluating and validating sites or applications. Among the results obtained, 54% of the responses referred to user experience (UX), 44% to usability, and 2% to accessibility, indicating that this area presents an opportunity for further studies.